Makna Kehadiran dan Jarak Emosional Suami-Istri dalam Komunikasi Keluarga Berbasis Teknologi Digital pada Pasangan Urban di Jakarta - Ayoedia Gita Citrayomie; Rosdiana, Rosdiana; Rizki Ayu Budipratiwi; Veronika Ita Karina Tarigan; Suci Indah Sari (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to understand the meaning of presence and emotional distance in marital relationships within the context of digital technology-based family communication. This study uses a qualitative approach with a phenomenological design, grounded in Symbolic Interactionism, supported by Social Presence Theory, Attachment Theory, and the concept of technoference. Data were obtained through in-depth interviews with three urban couples and analyzed using Miles and Huberman's interactive model. The results indicate that presence is defined as involvement, attention, and quality of response in interactions, both in person and through digital media. Emotional distance arises when attention is distracted by gadgets, responses feel minimal, or conversations lose depth. Internal meaning-making processes play a crucial role before actual responses emerge in relationships. Couples also employ relational strategies and negotiations, such as agreeing on gadget-free time and open communication, to maintain emotional closeness. These findings confirm that relationship dynamics in the digital age are shaped by ongoing processes of interaction and meaning-making.